HEPATOTOXICOPATHOLOGY EVALUATION OF DIMETHYLFORMAMIDE (DMF) ON MALE ALBINO RATS LIVERS - AL-Dleamy, H.Y.; Jawad, Z. J.M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This experiment was aimed to investigate the Toxicopathological effect of N, N-Dimethylformamide (DMF) (1/10LD50) on the adult male rats' liver. Sixteen adult male rats were used in this experiment. After acclimatization for two weeks, they were divided equally into two groups as follows: Group-C-control: Normal diet and water for 30 days (n=8 rats).Group-T1: DMF 645.5mg/kg. B.W as 1/10LD50 for30 days ( n=8rats ) , after thirty days collected blood for liver enzymes analysis then all animals killed at the end of the experiment and the liver samples saved at 10% formalin for histopathological preparation. The results showed that serum liver enzymes (ALP, ALT, and AST) concentrations of adult male rats after thirty days of oral DMF administration were significantly different (P